PERBEDAAN KONSENTRASI BELAJAR SISWA SEBELUM DAN SESUDAH DIBERI KONSELING FORMAT KELASIKAL - lase, Famahato; Marjohan, Marjohan; Syahniar, Syahniar (Pelita Bangsa Pelestari Pancasila, 2017)
This research aims at disclosing and explicating the differences and comparison the students’ concentration prior to and after being given the service of the classical format counseling. The data were 6th Primary School Children of Pembangunan Lab School Universitas Negeri Padang totaling 20 participants. The instruments made uses of collecting the data were observation sheets. The data analysis is undertaken using paired sample t statistics whilst for the pair samples is to test the difference the mean of the two samples. The method used is One – Group Pretest-Posttest Design.